COVID-19 and digitizing accounting education: empirical evidence from GCC. Issue 1 (5th February 2021) - Sarea, Adel; Alhadrami, Abdulla; Taufiq-Hail, Ghilan Al-Madhagy
Abstract : Purpose: The main objective of the study is to investigate the effect of COVID-19 on accounting education in the higher education (public and private universities) in the Gulf Cooperation Council (GCC). Design/methodology/approach: The study is explorative in nature conducted with quantitative survey approach and using purposive techniques in collecting data. The sample focuses on the teaching staff at public and private universities in (GCC), Kingdom of Saudi Arabia, United Arab Emirates, Bahrain, Kuwait, Oman and Qatar during the COVID-19. Findings: This study presumed to highlight some of the emergent issues faced during the pandemic pertaining the aspects of the COVID-19 and digitizing accounting education and its effect on future direction of digital education. Originality/value: To the best of the authors' knowledge, this study is the first academic paper to study the effect of COVID-19 on accounting education in the higher education in the GCC.